2011
DOI: 10.1007/s10995-011-0795-8
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in HIV Exposed Infants Significantly Improves Child Health: A Prospective Study

Abstract: Breastfeeding has been shown to benefit both maternal and child immune status. The impact of exclusive breastfeeding in the presence of HIV infection on maternal and child health is still unclear. Socio-economic factors make breast-feeding an important source of nutrition for an infant 6 months and under in the developing world. A prospective study was conducted to examine the impact of feeding mode on various maternal indices including anthropometry; body composition indicators (using FTIR); haematology and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
1
25
0
2
Order By: Relevance
“…In a South African study in which mothers self-selected feeding method, a lower risk of hospitalization was observed among breastfed infants in the first 14 weeks of life, but this difference was no longer significant by 6 months 18 . The BAN study in Malawi, in which all infants breastfed, found increased risk of morbidity after weaning 4 ; the same effect was observed in a Zambian trial of early abrupt weaning 19,20 .…”
Section: Discussionmentioning
confidence: 95%
“…In a South African study in which mothers self-selected feeding method, a lower risk of hospitalization was observed among breastfed infants in the first 14 weeks of life, but this difference was no longer significant by 6 months 18 . The BAN study in Malawi, in which all infants breastfed, found increased risk of morbidity after weaning 4 ; the same effect was observed in a Zambian trial of early abrupt weaning 19,20 .…”
Section: Discussionmentioning
confidence: 95%
“…In Tanzania, full breastfeeding (i.e., exclusive or predominant as compared with partial or none) was associated with a strong reduction in incidences of reported cough, acute diarrhea, fever, and outpatient visits between 0 and 6 mo of age but not of hospitalizations (27). In a clinic in South Africa, the incidence rate ratio of clinically diagnosed diarrhea was greatly reduced in 0-3-mo-old infants if they were breastfed (28). However, both of these analyses included both HIV-uninfected and -infected infants, and the latter infants are known to be very vulnerable to the absence of breastfeeding.…”
Section: Discussionmentioning
confidence: 98%
“…63 Although breastfeeding is a route of acquisition of HIV in the infant, breastfed infants had a significantly lower risk of diarrhoea and hospitalisation at 3 months. Breastfeeding was also significantly associated with better development scores and growth parameters in infants 64 and reduced mortality among infants and children. 65 …”
Section: # #mentioning
confidence: 91%